Connect with a community of experts and enthusiasts on IDNLearn.com. Discover in-depth and trustworthy answers to all your questions from our experienced community members.
Answer:
Simplifying
7x + 14 = 7(x + 2)
Reorder the terms:
14 + 7x = 7(x + 2)
Reorder the terms:
14 + 7x = 7(2 + x)
14 + 7x = (2 * 7 + x * 7)
14 + 7x = (14 + 7x)
Add '-14' to each side of the equation.
14 + -14 + 7x = 14 + -14 + 7x
Combine like terms: 14 + -14 = 0
0 + 7x = 14 + -14 + 7x
7x = 14 + -14 + 7x
Combine like terms: 14 + -14 = 0
7x = 0 + 7x
7x = 7x
Add '-7x' to each side of the equation.
7x + -7x = 7x + -7x
Combine like terms: 7x + -7x = 0
0 = 7x + -7x
Combine like terms: 7x + -7x = 0
0 = 0
Solving
0 = 0
Step-by-step explanation:
yw pls give brainliest